Reverse intestinal rotation: a rare case of volvulus around a vitelline duct remnant. (22nd September 2014) - Dreyer, Stephan; Kaczynski, Jakub; Hrobar, Petr; Collins, Patrick
Abstract : We present a rare case of reverse intestinal rotation with volvulus around a Meckel's diverticulum attached to a vitelline duct remnant. The diagnosis was established by CT. The patient was treated with exploratory laparotomy and small bowel resection. The patient made a full recovery and was discharged home on the seventh postoperative day.